LITERACY BASED ON THE PRINCIPLES OF VOICE, CHOICE AND OWNERSHIP TO STRENGTHEN LITERACY IN ELEMENTARY SCHOOL - Firda Dwi Lestari; Anang Santoso; Shirly Rizki Kusumaningrum; Ade Eka Anggraini; Dyana Maftuhatu Rosyidah (Universitas Islam Negeri Mataram, 2026)
This study aims to describe the implementation of a literacy program grounded in the principles of voice, choice, and ownership to strengthen literacy among 4th-grade students at SD Negeri Kepanjen 2 Jombang. The study used a mixed-methods approach with an explanatory sequential design, involving 32 students as quantitative respondents and 11 qualitative informants. Data collection techniques include literacy tests, participatory observations, semi-structured interviews, and documentation. Quantitative data were analyzed using descriptive statistics and a paired sample t-test, while qualitative data were analyzed using the Miles and Huberman model. The study found that program planning involves students in the needs analysis: 78 percent want a choice of books, and 82 percent are interested in creating literacy products. The program’s implementation includes morning literacy, reading circles, writing workshops, and wall magazine projects, with high participation rates (76-92 percent). The impact of the implementation showed a significant increase in reading ability from 65 to 85 (31 percent), and in writing, from 58 percent to 88 percent of students were able to write structured paragraphs. Reading interest increased from 1.2 to 3.5 books per week. There was an increase in students’ confidence, responsibility, creativity, and collaborative abilities, indicating that voice, choice, and ownership literacy programs were effective in improving students’ literacy and social-emotional competence